CFD Simulation of Slugs Dissipation for the Inlet Pipeline of Cylindrical Cyclone Separator. (2015) - Luo, Xiaoming; Wang, Yibin; He, Limin; Geng, Geng
Abstract: The user defined function (udf) of Fluent simulator was adopted to define initial conditions of transient slug flow, and a simulation method, which was based on VOF multi flow model, of slug flow was developed to conduct numerical simulation research on slug dissipation in inlet rectifier pipe of cylindrical cyclone separator. Flow parameters of initial inlet slug were given by establishing a one-dimensional steady slug flow model. This paper simulated the dissipation process of hydrodynamic slug in rectifier pipes, where the slug dissipated under the co-effect of diameter-expanding pipes and downward inclined pipes. The centrifugal force field in downward inclined helical pipes ensured the inclination and stability of the gas-liquid interface at the same time.